Multi‐material additive manufacturing of embedded low‐profile antennas. Issue 20 (1st October 2015) - Pa, P.; Larimore, Z.; Parsons, P.; Mirotznik, M.
Abstract : A low‐profile antenna that includes an integrated artificial magnetic conducting (AMC) ground plane is presented and is fully fabricated using multi‐material additive manufacturing. It is shown that combining standard fused deposition modelling with conductive micro‐dispensing printing enable one to realise mechanically robust antenna systems that contain spatially variable dielectric properties and intricate three‐dimensional conducting networks. To illustrate this capability, a low‐profile antenna is designed, fabricated, and experimentally validated, consisting of a standard 2.6 GHz half wavelength printed dipole, balun, and AMC ground plane.